Properties of gas detonation ceramic coatings and their effect on the osseointegration of titanium implants for bone defect replacement. Issue 18 (15th September 2021) - Klyui, Nickolai I.; Chornyi, Volodymyr S.; Zatovsky, Igor V.; Tsabiy, Liana I.; Buryanov, Alexander A.; Protsenko, Volodymyr V.; Temchenko, Volodymyr P.; Skryshevsky, Valeriy A.; Glasmacher, Birgit; Gryshkov, Oleksandr
Abstract: An optimal performance of bone implants with bioceramic coatings is closely related to the surface modification technology. For the first time, we have evaluated a gas detonation deposition (GDD) approach to obtain biocompatible ceramic coatings based on bioglass (BG) and calcium phosphates on Ti-based alloys as prospective materials towards their application for the development of bone implants. For the production of the coatings, hydroxyapatite (HA), HA metal-substituted (containing Ag +, Cu 2+, or Zn 2+ ) and tricalcium phosphate (TCP) were synthesized and characterized. Pure powders and their combination with BG were used to obtain coatings on a Ti–6Al–4V alloy using the developed automatized GDD setup. The microstructure, phase and chemical composition of the produced coatings were studied using XRD, SEM-EDS and Raman spectroscopy. The produced coated materials were evaluated in vivo in Wistar rats to analyze a reparative osteogenesis over a period of 12 weeks. The results regarding the optimization of the GDD method indicate its high productivity, as confirmed by high deposition rates. The highest deposition rate was observed for the coatings obtained from the HA metal-substituted powders. The results revealed a partial transformation of a HA phase to an α-TCP phase during the deposition, with a prevalence of the HA-phase in the coatings. According to the histological evaluation, the reparative osteogenesis occurs through the perimeter of the titanium implants, whereas the regeneration level increases from the 4th to the 12th week. The highest osteointegration level was detected for the implants coated with a biocomposite consisting of BG, HA and TCP. The results of the current study demonstrate an effectiveness of the GDD method to produce biocompatible coatings on Ti-based alloys. This provides excellent prerequisites towards the application and standardization of the GDD technology to manufacture bone implants for bone fixation and defect replacement, as well as the development of dental implants.